Co-electrodeposition of RuO2–MnO2 nanowires and the contribution of RuO2 to the capacitance increase1. Issue 23 (21st June 2015) - Gui, Zhe; Gillette, Eleanor; Duay, Jonathon; Hu, Junkai; Kim, Nam; Lee, Sang Bok
<x xml:space="preserve">Abstract</x> Co-electrodeposition produces RuO2–MnO2 composite nanowire electrodes with different RuO2 loading amounts. RuO2's contribution to the composite is revealed to be conductivity rather than intrinsic capacity.